Application of MRI to identify metabolic and physiological correlates of human ageing and inactivity - Hale, Andrew (2018)
Physical inactivity has been linked to poor health and disease progression, particularly in older people. This has led to an increasing interest in the effects of physical activity, physiological function and ageing. Importantly, negative health traits generally attributed to ageing, such as frailty, cognitive decline and brain atrophy, may in part result from decreased habitual physical activity levels, and be preventable with increased exercise. Here, we use magnetic resonance imaging (MRI) techniques to quantify the cortical haemodynamic and metabolic responses to acute low/moderate intensity exercise in healthy young and older volunteers, to investigate how this response is influenced by ageing and cardiorespiratory fitness. In addition, structural MRI is used to investigate global and regional grey matter volume, and cortical thickness in young and older adults, and to assess its association with age and cardiorespiratory fitness. In the final Chapter, methods are developed to study the impact of a 16-day limb immobilisation on brain and muscle function using ultra-high field, 7 T MRI. Functional magnetic resonance imaging (fMRI) is used to assess changes in brain motor cortex function over the course of 16 days of upper limb immobilisation, and assess whether any changes are observed associated with the loss of voluntary handgrip strength over the same time period. Muscle MRI is performed to assess changes in muscle cross sectional area, and muscle magnetic resonance spectroscopy (MRS) developed with the aim of quantifying changes in forearm muscle IMCL and EMCL content over the immobilisation period.